2022
DOI: 10.1039/d2na00542e
|View full text |Cite
|
Sign up to set email alerts
|

Precise size-control and functionalization of gold nanoparticles synthesized by plasma–liquid interactions: using carboxylic, amino, and thiol ligands

Abstract: Using gold nanoparticles (GNPs) in high-standard applications requires GNPs fabricated of high quality of size and surface properties. Plasma-liquid interactions (PLIs) own the unique ability to synthesize GNPs without using...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…The XPS survey spectrum of UiO-66-NH-SH (1) confirms the presence of expected elements (Zr, C, O, N, S) in the thiol MOF and the introduction of the Ag in catalyst Cat 2 (Figure a). The Ag 3d spectrum of Cat 2 shows peaks at 368.2 and 374.2 eV with a gap of 6.0 eV, corresponding to Ag 3d 5/2 and Ag 3d 3/2 , respectively, confirming the presence of the zero oxidation of silver (Ag 0 ; Figure b). , The characteristic peak of thiol was observed as an S 2p peak in UiO-66-NH-SH (1) (164.5; Figure c), which shifted to 164.1 (Figure d) in Ag nanoparticle-functionalized Cat 2, confirming the strong interaction between thiol and Ag, which correlates well with the previously reported literature. , In the case of N 1s and O 1s, a very slight shift is observed between the thiol MOF and the catalyst, which excludes the strong interaction between N, O, and Ag (Figure d) . The comparison between thermogravimetric analysis (TGA) plots of parent MOF UiO-66-NH 2 , thiol-introduced MOF UiO-66-NH-SH (1), and Ag-functionalized catalyst Cat 2 shows that the thermal stability of the catalyst was retained upon silver functionalization (Figure S9).…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…The XPS survey spectrum of UiO-66-NH-SH (1) confirms the presence of expected elements (Zr, C, O, N, S) in the thiol MOF and the introduction of the Ag in catalyst Cat 2 (Figure a). The Ag 3d spectrum of Cat 2 shows peaks at 368.2 and 374.2 eV with a gap of 6.0 eV, corresponding to Ag 3d 5/2 and Ag 3d 3/2 , respectively, confirming the presence of the zero oxidation of silver (Ag 0 ; Figure b). , The characteristic peak of thiol was observed as an S 2p peak in UiO-66-NH-SH (1) (164.5; Figure c), which shifted to 164.1 (Figure d) in Ag nanoparticle-functionalized Cat 2, confirming the strong interaction between thiol and Ag, which correlates well with the previously reported literature. , In the case of N 1s and O 1s, a very slight shift is observed between the thiol MOF and the catalyst, which excludes the strong interaction between N, O, and Ag (Figure d) . The comparison between thermogravimetric analysis (TGA) plots of parent MOF UiO-66-NH 2 , thiol-introduced MOF UiO-66-NH-SH (1), and Ag-functionalized catalyst Cat 2 shows that the thermal stability of the catalyst was retained upon silver functionalization (Figure S9).…”
Section: Resultsmentioning
confidence: 57%
“…40,94 The characteristic peak of thiol was observed as an S 2p peak in UiO-66-NH-SH (1) (164.5; Figure 3c), which shifted to 164.1 (Figure 3d) in Ag nanoparticle-functionalized Cat 2, confirming the strong interaction between thiol and Ag, which correlates well with the previously reported literature. 40,95 In the case of N 1s and O 1s, a very slight shift is observed between the thiol MOF and the catalyst, which excludes the strong interaction between N, O, and Ag (Figure 3d). 96 The comparison between thermogravimetric analysis (TGA) plots of parent MOF UiO-66-NH 2 , thiol-introduced MOF UiO-66-NH-SH (1), and Ag-functionalized catalyst Cat 2 shows that the thermal stability of the catalyst was retained upon silver functionalization (Figure S9).…”
Section: ■ Introductionsmentioning
confidence: 94%
“…Because the convection and diffusion in the liquid are low, the reactive species concentrate into a high concentration in a small region on the scale of μm below the gas−liquid interface. 21,22,65 In addition, this region is also accompanied by intense local heating due to the dissociation quenching process of electronically excited N 2 molecules or the exothermicity of OH formation from the discharge, which could reach 2000−3000 K. 20,24 The condition of this region could be similar to that of a piranha solution at a microscale below the plasma−liquid interface. Detailed physicochemical properties of PCL and so on can be found in detail in refs 21− 23, .…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Recent studies using plasma-induced reduction have shown that the resultant diameter is inversely proportional to the ligand solution concentration. 34 Moreover, the strength of the affinity of the ligand for the Au surface determines the strength of the effect. The peptides in this study synthesized small AuNPs at relatively low concentration, without any reducing agent, suggesting that the peptide potency was high compared to that of traditional ligands such as citrate.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Generally, in the chemical synthesis of nanoparticles, the ligand concentration is increased to produce small AuNPs. Recent studies using plasma-induced reduction have shown that the resultant diameter is inversely proportional to the ligand solution concentration . Moreover, the strength of the affinity of the ligand for the Au surface determines the strength of the effect.…”
Section: Discussionmentioning
confidence: 99%